Abstrakcyjna teoria modeli – semantyczne ujęcie logiki - Wójtowicz, Krzysztof (Filozofia Nauki, 2015)
The article presents main motivations underlying investigations into abstract model theory. It introduces basic technical notions and describes some philosophical problems associated with the theory.